Effectiveness of marine protected areas as a management tool for the management of the seas of Malaysia - Ali, Jamal; Ariff, Shahariah; K.V.S.N Viswanathan, K. Kuperan; Islam, Rabiul (INSInet Publications, 2013)
This study analysis the need for more research on marine protected areas and how regulation and recreational activities of marine protected areas, using fish stock indicators.Secondary data was collected from the Department of Fisheries Kedah and Department of Marine Park, Kedah, Malaysia. The finding shows that the key elements for good management are implementing an educational and awareness program, enforcing Marine Park regulations, limiting visitor's use, establishing monitoring and evaluation programs.Coupled with the promotion of alternative activities and alternative islands to disperse pressure on the reefs of Pulau Payar Marine Park, these actions can help to ensure that the tourism industry at the marine park is environmentally, socially and economically sustainable.